"Consent Is Sexy": exploring the portrayal of prosocial sexuality messages in youth-oriented series. Issue 3 (3rd July 2022) - Maes, Chelly; Vandenbosch, Laura
ABSTRACT: Content analyses on sexual messages in youth-oriented series have traditionally focused on the distribution of negative or antisocial sexual messages. As such, the potential of youth-oriented series to promote prosocial sexual messages (PSM) has been neglected. Grounded in the 3 AM model, this content analysis fills this gap in the literature by examining the occurrence of PSM in youth-oriented series (e.g. Elite ) on Netflix. A total of 126 characters (52% male, 48% female) and 3, 151 scenes in 65 episodes were coded. The results indicate that PSM were promoted 4 times per episode (i.e. average length was 36 minutes) and were distributed by more than half of the characters. PSM also significantly co-occurred with antisocial sexual messages (ASM) in scenes, suggesting that sexual messages may operate as a "mixed" socialization agent for adolescents' sexuality development. Further, characters in comedies and non-heterosexual characters more often distributed PSM than respectively characters in dramas and heterosexual characters. The promotion of PSM did not vary by characters' gender. Implications of these findings in terms of audience effects and suggestions for future research are further discussed. IMPACT SUMMARY: Prior State of Knowledge: While negative sexual messages in youth-oriented television series have been studied extensively, little is known about these television series' potential to promote positive sexual messages. Novel Contributions: This content analysis addresses this gap in the literature. Positive sexual messages are frequently promoted in youth-oriented television series and co-occur with negative sexual messages. Also, they challenge the heterosexual script. Practical Implications: For parents and practitioners who view television as a tool for learning about sexuality, these results suggest that negative and positive sexual messages in television series co-occur. Providing explanations of these messages may be relevant for young viewers.